A cohort study on use of the spot urine calcium-creatinine ratio for prediction of antepartum preeclampsia among high-risk pregnant women in Delta State, Nigeria: Spot urine calcium-creatinine ratio in pregnant women - Jagu, Lloyd; Orugbo, V. Peter; Okonta, Patrick (Journal of Surgery and Medicine, 2022)
Background/Aim: Preeclampsia is a multisystemic disorder, which significantly contributes to maternal and fetal morbidity and mortality, especially in developing countries where it accounts for about one-third of maternal mortality cases. Predicting its occurrence will reveal a sizeable population of pregnant women who will undoubtedly benefit from prevention. The ideal screening marker for the disease is still being investigated. The urine calcium-creatinine ratio (CCR) is an inexpensive, simple, and easily assayed biomarker. This study determined the accuracy of the spot urinary calcium-creatinine ratio in predicting the occurrence of preeclampsia. Methods: This was a prospective cohort study conducted in Delta State, which involved four healthcare facilities in Nigeria. A total of 138 pregnant women between 8 and 18 weeks gestation were recruited. Urine samples were obtained at 18 weeks to assay their CCR, and patients were followed up weekly for blood pressure measurement and dipstick urinalysis until delivery. Results: The mean spot urine CCR in this study was 0.225 (0.101). It was significantly lower in women who developed preeclampsia compared to normotensive women (P < 0.001). Multiple logistics regression analysis showed that the association between urine CCR and occurrence of preeclampsia was statistically significant. At a receiver operating characteristic cutoff of ≤ 0.1065, CCR had a sensitivity of 75%, specificity of 91.3%, positive predictive value (PPV) of 35.3%, and negative predictive value (NPV) of 98.3%. The low PPV of 35.3% can be explained by the low prevalence of preeclampsia (5.78%) in the study population. Conclusion: In conclusion, the poor PPV of the urine CCR was due to the low prevalence of preeclampsia in the study. However, in considering all women at risk, urine CCR may be a good prognostic marker when the illness prevalence is substantial.